2018
DOI: 10.1016/j.mtla.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Improving ageing kinetics and precipitation hardening in an Al-Mg-Si alloy by minor Cd addition

Abstract: This study reports significant improvements in both the age hardening kinetics and peak hardness of an Al-Mg-Si alloy by microalloying with 0.06 at.% Cd. A detailed high-angle annular dark-field scanning transmission electron microscopy study shows that most of the needle-shaped hardening precipitates β" (~82%) formed in the Cd-containing alloy are attached to or around Cd-rich precipitates, indicating that the Cd-rich precipitates can act as effective nucleation sites for needle-shaped precipitates, and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…The authors reported the enhanced precipitation of the b'' metastable phase due to increased quenched-in vacancies. Though the heat treatment modifications like pre-ageing, intermediate quenching, etc., suppress the determinantal effects of natural ageing, the alloying addition with Ge [52,53], Cu [10,11,54,55], Cd [56], Ag [57][58][59], Zn [60], Li [52], Sc and Zr has recently attracted attention due to the accelerated ageing response and significant improvement in strength. The enhanced ageing response is related to the modification in the precipitation sequence by the alloying additions.…”
Section: Strengthening Due To Ordered Precipitatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported the enhanced precipitation of the b'' metastable phase due to increased quenched-in vacancies. Though the heat treatment modifications like pre-ageing, intermediate quenching, etc., suppress the determinantal effects of natural ageing, the alloying addition with Ge [52,53], Cu [10,11,54,55], Cd [56], Ag [57][58][59], Zn [60], Li [52], Sc and Zr has recently attracted attention due to the accelerated ageing response and significant improvement in strength. The enhanced ageing response is related to the modification in the precipitation sequence by the alloying additions.…”
Section: Strengthening Due To Ordered Precipitatesmentioning
confidence: 99%
“…Due to similar electronic properties, Ge was reported to replace Si atoms in the b'' phase [53], while Li was reported to substitute Mg sites in the b'' structure [52]. Cd forms Cd-rich precipitates in the early stage of artificial ageing and acts as nucleation sites for needle-shaped b'' precipitates that lead to the observed Q'/C type triangular sub-units in the matrix [56]. HAADF-STEM further reveals that Cd-atoms incorporated into b'' precipitates leads to a disordered structure.…”
Section: Strengthening Due To Ordered Precipitatesmentioning
confidence: 99%
“…wherein the first term on the right of Eq. [10], vð rÞ is the approximation for the growth rate of particles, which can be described with the classic Zener equation. [35] The second term corresponds to the change of r contributed by dissolution of u(r*)dr* particles with radius r*+dr* >r>r*.…”
Section: A Nucleationmentioning
confidence: 99%
“…According to Eq. [10], an increase of the mean particle radius is contributed by the Zener growth equation and dissolution of particles with instantaneous radius smaller than r* at late aging (coarsening) stage, wherein the nucleation rate at this stage is approaching~0, with no contribution of newly nucleated particles to mean particle radius. As a result of the same aging temperature, the diffusion controlled Zener growth equation is not supposed to cause large discrepancy in the growth [49] 1.342 9 10 À19 m 2 /s Diffusion Mobility of Si in Matrix [49] 2. rate of the two precipitates.…”
Section: A Model Prediction Of B¢¢ Precipitationmentioning
confidence: 99%
See 1 more Smart Citation